PERFORMANCE ANALYSIS OF HELICAL COIL AND INNOVATIVE TUBES HEAT EXCHANGER WITH PHASE CHANGE MATERIALS: NUMERICAL AND EXPERIMENTAL STUDY - Atheer S. Hassoon (Journals Park Publishing, 2025)
This study presents a numerical and experimental analysis of two models of latent heat storage systems using heat exchangers with phase change material (PCM). The models utilized were helically coiled tube heat exchangers (HCT-HX) and innovative tube heat exchangers (IT-HX). The models were analyzed for two distinct injections of Heat Transfer Fluid (HTF) from the upper section of the models. The comparison of both scenarios showed that varying the Heat Transfer Fluid inlet while maintaining a constant mass flow rate significantly influences the duration of the melting process. In comparison, the melting time for (HCT-HX) decreases by 11.2%, whereas (IT-HX) results in a 24% delay in melting. The model in (HCT-HX) has the best thermal performance and the quickest melting time because of the geometry of it. A high degree of concordance was seen when the numerical and experimental outcomes were compared.
Keywords: IT-HX, HCT-HX, PCM, melting time, latent heat storage.